DEVELOPMENT OF DIGITAL MEDIA “TEMA TARI” - Triwahyuni Triwahyuni; Dwi Kameluh Agustina; Minto Santoso (JOSAR (Journal of Students Academic Research), 2020)
This research is titled the development of digital “Tema Tari”. The results of research in primary schools conducted by interviews showed the media used were less attractive and still conventional. 93% of students have a smartphone left in the teacher’s locker. Students are found to be less active in learning so many students get gredes below minimum completeness criteria. This study aims to determine the development of digital learning media “Tema tari” to improve student learning outcomes in primary scools and measure the achievement of improving student learning outcomes in these elementary schools. In this research, the method used is the R&D method adopted from Sugiono. Based on the validation results obtained: (1) The results of the validation test of the design expertise 82,68%. (2) Validity results of material experts 92%. (3) Validity test results of linguists 86,05 %. The posttest score is better than the pretest score. Average yield of N-gain of 0.77 is the category of a high rise. From the above data it can be concluded that this media is declared feasible and can improve learning outcomes.